(untitled) (Baghdad Science Journal, 2011)
Several azo dyes were synthesized through coupling reaetion of some substituted phenols and B.naphthol with diazonium salt of 2- amino-1,3-4- thiadiazol -5- thiol. All the synthesized compounds during this work were characterized using some speetral data (F.TIRand UV)andM.P . 2-[4 –Hydroxy napthyl-azo ] -1,3,4-Thiadiazol -5-Thiol • 2- [2– hydroxy –4- NO2 – phenyl- azo]- 1,3,4 - Thiadiazol –5-Thiol. • 2- [3–Amino-4-Hydroxy phenyl –azo]-1,3,4 - Thiadiazol –5-Thiol. . • 2-[2–Amino-4-Hydroxy phenyl -azo]-1,3,4 - Thiadiazol –5-Thiol . • 2- [3–Amino-6- Hydroxy phenyl -azo]-1,3,4 - Thiadiazol –5-Thiol. • 2-[2– Hydroxy- 5 – chloro – Pheny - azo]- 1,3,4 - Thiadiazol –5-Thiol . • 2- [4– Hydroxy phenyl -azo] -1,3,4 - Thiadiazol –5-Thiol . • 2- [ 3– Bromo – 6 – Hydroxy - phenyl –1-azo] – 1,3,4, Thiadiazol –5-Thiol .